Refining molecular analysis in the pathways of colorectal carcinogenesis. - Rowan, A; Halford, S; Gaasenbeek, M; Kemp, Z; Sieber, O; Volikos, E; Douglas, E; Fiegler, H; Carter, N; Talbot, I; Silver, A; Tomlinson, I (2005)
BACKGROUND and AIMS: In the stepwise model, specific genetic and epigenetic changes accumulate as colorectal adenomas progress to carcinomas (CRCs). CRCs also acquire global phenotypes, particularly microsatellite instability (MSI) and aneuploidy/polyploidy (chromosomal instability, CIN). Few changes specific to MSI-low or CIN+ cancers have been established. METHODS: We investigated 100 CRCs for: mutations and loss of heterozygosity (LOH) where appropriate, of APC, K-ras, BRAF, SMAD4, and p53; deletion on 5q around APC and 18q around SMAD4; total chromosomal-scale losses and gains; MSI; and CIN. RESULTS: As expected, CIN- cancers had fewer chromosomal changes overall than CIN+ lesions, but after correcting for this, 5q deletions alone predicted CIN+ status. 5q deletions were not, however, significantly associated with APC mutations, which were equally frequent in CIN+ and CIN- tumors. We therefore found no evidence to show that mutant APC promotes CIN. p53 mutations/LOH were more common in CIN+ than CIN- lesions, and all chromosomal amplifications were in CIN+ tumors. CIN- cancers could be subdivided according to the total number of chromosomal-scale changes into CIN-low and CIN-stable groups; 18q deletion was the best predictor, being present in nearly all CIN-low lesions and almost no CIN-stable tumors. MSI-low was not associated with CIN, any specific mutation, a mutational signature, or clinicopathologic characteristic. CONCLUSIONS: Overall, the components of the stepwise model (APC, K-ras, and p53 mutations, plus 18q LOH) tended to co-occur randomly. We propose an updated version of this model comprising 4 pathways of CRC pathogenesis, on the basis of 5q/18q deletions, MSI (high/low), and CIN (high/low/stable).